آثار الإجهاض في الفقه الإسلامي - أسماء ا زوي; شادية ا زوش; مسعودة سقني (University of Eloued-جامعة الوادي, 2017)
عنونت هذه الدراسة: "آثار الإجهاض في الفقه الإسلامي"، وقد قسمت إلى أربعة مباحث؛ حيث عُني المبحث الأ ول: بتعريف الإجهاض، وذكر حكم الإجهاض في كل مرحلة من مراحل الحمل، وجاء في المبحث الثاني بيان المسؤولية الجنائية والمسؤولية المالية فحددنا المسؤولين عن عملية الإجهاض، والعقوبة المقرر لذلك، أما المبحث الثالث فقد عُني بذكر حكم الصلاة، وتغسيل، وتكفين، ودفن الجنين امجهه،، والمبحث الراب تناولنا في ههارة المرأة امجهه،، وحالات وقوع الطلاق والخروج من العدة بالإجهاض. : Resume I titled this study "Abortion traces in Islamic fiqh"and it is classified in four researches. The first one is about the definition of about and its judement in each stage of pregnanuj، the second researeh is to shon criminal and financial lsabilities and to identify the reponsible of this process and its punishemwt. The third research focused on hon to deal with the abdominal fetus: praying; washing; shrouding burying…، and in the fourth one: we talked abont the purity of the aborted woman; cases of divores and the end of "edde" because of aboitin.
مذكرة ليسانس
Keywords: الاجهاض /الفقه الاسلامي /الاثار; Avortement / Jurisprudence islamique / effets